WHAT CONSTITUTES MATERIAL COST OF PRODUCTION? - Castenholz, W. B. (The Accounting Review, 1958)
Abstract The article presents information on material cost of production. Materials to be manufactured must also be purchased, received, stored and delivered to the production centers; none of these expenditures are "manufacturing" costs, regardless of the fact that some manufacturers include them as part of manufacturing expense or burden. The latter practice is, decidedly, an improper incidence of expense. In this manner, the inventories of raw materials and stores would always remain at delivered cost, as Goods in Process account was charged at that cost. The costs of purchasing, receiving and storage would then be charged to Goods in Process, as an additional material cost. The procedure means that the costs of purchasing, receiving and storage, as these occurred each month, would be charged to an account but labeled as "Unapplied Material Burden." These costs, obviously, would be absorbed into Goods in Process each month on the basis of the value of the materials used.